P202 The acceptability of self-sampling at home for Chlamydia trachomatis and Neisseria gonorrhoeae in men and women; results from the feasibility study to determine the time taken for NAATs tests to become negative following treatment for Chlamydia trachomatis and Neisseria gonorrhoeae in men and women. (30th June 2016) - Sultan, Binta; Oakland, Clare; Brima, Nataliya; Patel, Hemi; Schembri, Gabriel; Ison, Cathy; Benn, Paul
Abstract : Background/introduction: Self-sampling with nucleic acid amplification tests(NAATs) for detection of chlamydia(CT) and gonorrhoea(NG) is increasingly being used in clinics, with much success. There is some data to suggest that it is acceptable to patients. Aim(s)/objectives: To assess symptoms, sexual behaviour and the acceptability of self-taken swabs for CT and NG, among participants in the 'Time to test of cure study for CT and NG'. Methods: Individuals who had a positive NAAT test for CT and/or NG were eligible. Self-taken specimens from the site of infection were collected at home. Data about sexual behaviour, symptoms and acceptability of home testing with self-taken samples was collected from questionnaires. Results: 102 men (87 MSM) and 52 women were recruited to the study, 84 had NG infection and 71 had CT infection. The median age was 28 years. Unprotected sexual intercourse in the last month was reported by 68% of MSM, 56% of heterosexual men and 51% of women. Symptoms were reported by 25% of MSMs, 50% of heterosexual men and 51% of women. 86% of participants found the information clear and easily understandable. 85% felt confident taking their own samples. 58% found the samples easy to take, 75% were happy to take their own swabs and 78% were happy to take samples at home. Discussion/conclusion: This data highlights the need for screening of asymptomatic patients and provides data to support that self-taken sampling is acceptable to patients. It also provides evidence to support home testing for CT and NG. Therefore allowing for greater access to testing and treatment and reducing the burden of infection in the community.